Identification of Livelihood Assets of the Tanggulangin Fishing Community Klirong sub-district Kebumen District - Zulaikhah Fitri; Sugihardjo Sugihardjo; Agung Wibowo (CIC Lembaga Riset dan Konsultan Sosial, 2021)
ABSTRACT Tanggulangin Fishing Community still depends on the catch of fish even though the available resources can be properly utilized and managed to improve livelihoods. A sustainable livelihood approach is needed to determine fishermen in their livelihoods that are uncertain and depending on the season. Identification of sustainable livelihood assets in order to survive in fishing and famine seasons. The research method used is descriptive qualitative. The determination of informants is done by using the snowball technique. Data collection using in-depth interview techniques, participant observation and documentation. The data were analyzed interactively and the validity of the data was obtained by using triangulation techniques of sources and methods. The sustainable livelihood assets carried out by the Tanggulangin Fishing Community are utilizing financial and social capital during the fishing season, while natural capital during the low season is amidst physical and human capital constraints. Physical capital constraints, namely still using traditional fishing facilities, have no effect because they still want to maintain the balance of the marine ecosystem. Human capital constraints that are not open to information and skills so that an increase in human capital (knowledge, skills and experience) is needed. Keyword: fishing community; identification; livelihood assets ABSTRAK Rukun Nelayan Tanggulangin masih bergantung pada hasil tangkapan ikan padahal sumber daya yang tersedia dapat dimanfaatkan dan dikelola dengan baik untuk meningkatkan penghidupan. Pendekatan penghidupan berkelanjutan dibutuhkan guna menentukan nelayan dalam mempertahankan hidupnya yang tidak menentu dan tergantung pada musim. Pengidentifikasian aset penghidupan berkelanjutan agar dapat bertahan hidup pada musim melaut dan paceklik. Metode penelitian yang digunakan adalah kualitatif deskriptif. Penentuan informan dilakukan dengan teknik snowball. Pengumpulan data menggunakan teknik wawancara mendalam, observasi partisipan dan dokumentasi. Analisis data dilakukan secara interaktif dan validitas data diperoleh dengan teknik triangulasi sumber dan metode. Aset penghidupan berkelanjutan yang dilakukan oleh Rukun Nelayan Tanggulangin adalah memanfaatkan modal finansial dan modal sosial pada musim melaut sedangkan modal alam pada musim paceklik ditengah hambatan modal fisik dan manusia. Hambatan modal fisik yaitu masih menggunakan sarana penangkapan ikan secara tradisional tidak berpengaruh karena mereka tetap ingin menjaga keseimbangan ekosistem laut. Hambatan modal manusia yang kurang terbuka terhadap informasi dan keterampilan sehingga dibutuhkan peningkatan modal manusia (pengetahuan, keterampilan dan pengalaman). Kata Kunci: aset penghidupan; identifikasi; rukun nelayan